2021
DOI: 10.3389/fcimb.2021.772311
|View full text |Cite
|
Sign up to set email alerts
|

Effective Genome Editing in Leishmania (Viannia) braziliensis Stably Expressing Cas9 and T7 RNA Polymerase

Abstract: Until 2015, loss-of-function studies to elucidate protein function in Leishmania relied on gene disruption through homologous recombination. Then, the CRISPR/Cas9 revolution reached these protozoan parasites allowing efficient genome editing with one round of transfection. In addition, the development of LeishGEdit, a PCR-based toolkit for generating knockouts and tagged lines using CRISPR/Cas9, allowed a more straightforward and effective genome editing. In this system, the plasmid pTB007 is delivered to Leis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…braziliensisthat express the exogenous SpCas9 protein from the episomal pTB007-Viannia plasmid. 17 Therefore, we consider that this immunological tool will facilitate studies based on CRISPR/Cas in this research parasitic model and various other biological samples.…”
Section: Discussionmentioning
confidence: 99%
“…braziliensisthat express the exogenous SpCas9 protein from the episomal pTB007-Viannia plasmid. 17 Therefore, we consider that this immunological tool will facilitate studies based on CRISPR/Cas in this research parasitic model and various other biological samples.…”
Section: Discussionmentioning
confidence: 99%
“…Until 2015, double homologous recombination of laboriously generated vectors was the only way to screen for function in Leishmania parasites. However, supplementation of the genome with endogenous ( L. major, L. mexicana ( Beneke et al., 2017 ) and L. braziliensis ( Espada et al., 2021 )) or episomal ( L. mexicana , L. major ( Beneke et al., 2017 ), L. tarentolae ( Turra et al., 2021 ), L. donovani ( Martel et al., 2017 ) and L. braziliensis ( Adaui et al., 2020 ) polymerase expression enabled the use of Cas9 mediated genome editing. Targeting a library of kinases in L. mexicana promastigotes, and using BarSeq to track mutants, showed that 79% of the kinome is dispensable for promastigote growth in culture, while 21% were refractory to gene knockout ( Baker et al., 2021 ).…”
Section: Functional Screeningmentioning
confidence: 99%
“…On the other hand, several limitations include the potential loss of fluorescence during the fixation process and interference with tagged-protein expression, folding, functionality, and/or subcellular targeting ( Chalfie et al., 1994 ; Palmer & Freeman, 2004 ; Swenson et al., 2007 ) (Table 1). In regards to the functional interference, in locus reinsertion of a fluorescent protein-tagged PF16 in the L. braziliensis PF16 knockout line showed only partial recovery of wild-type flagellar motility phenotype ( Espada et al., 2021 ). Likewise, regarding the subcellular targeting interference, the amino acid permease 3 (aap3) was located on the surface membrane of L. donovani promastigotes by tagging aap3 with fluorescent proteins at first ( Shaked-Mishan et al., 2006 ).…”
Section: Enzymatic Systemsmentioning
confidence: 99%
“…Such advancements enabled the investigation of targeted gene expression and function, as well as the subcellular localization of the encoded protein of interest using various tags. However, the results obtained from manipulating heterologous reporter gene must be carefully analyzed since the introduction of exogenous sequences may interfere with the endogenous sequences, which then could result in misleading observations and conclusions ( Zhang et al., 2003 ; Folgueira & Requena, 2007 ; Kovtun et al., 2010 ; Goldman-Pinkovich et al., 2016 ; Espada et al., 2021 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%